Action research : models, methods, and examples - Willis, Jerry W.; Edwards, Claudia (Applied research in education and the social sciences., 2014)
The first three chapters of Action Research: Models, Methods, and Examples covers the history, foundations, and basics of conducting action research projects. In those chapters you will learn about the origins of action research as well as about the different methods and models of action research - from the original approaches used by Kurt Lewin and his students in the 1940s and 1950s to the diversity of current approaches to AR that are used to develop both solutions to real world problems and to construct a better understanding of important issues and concern in communities, schools, businesses, and organizations.The nine chapters in the second part of the book illustrate the many ways action research is practiced today. Those chapters illustrate the use of action research methods to accomplish everything from individual personal professional development to changing policies and practices in large organizations and systems.The chapters detail many specific methods of doing AR such as participatory action research, emancipatory action research, designbased action research, collaborative inquiry, and many others.